2010
DOI: 10.1002/humu.21364
|View full text |Cite
|
Sign up to set email alerts
|

Generation and analysis of the thiazide-sensitive Na+-Cl− cotransporter (Ncc/Slc12a3) Ser707X knockin mouse as a model of Gitelman syndrome

Abstract: Gitelman syndrome (GS) is characterized by salt-losing hypotension, hypomagnesemia, hypokalemic metabolic alkalosis, and hypocalciuria. To better model human GS caused by a specific mutation in the thiazide-sensitive Na(+) -Cl(-) cotransporter (NCC) gene SLC12A3, we generated a nonsense Ncc Ser707X knockin mouse corresponding to human p.Ser710X (c.2135C>A), a recurrent mutation with severe phenotypes in Chinese GS patients. Compared with wild-type or heterozygous littermates, homozygous (Hom) knockin mice full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 49 publications
(80 reference statements)
3
49
0
Order By: Relevance
“…Reduced T60M-NCC expression in MDCK cells, markedly diminished Ncc abundance in the DCT cells of Ncc T58M/T58M mice, and decreased urinary NCC excretion, an index of membrane-expressed NCC, in GS patients all indicated that T60M led to reduced NCC expression primarily through post-translational modification (phosphorylation) rather than translational change. Because increased late DCT volume was found in Ncc T58M/T58M mice, similar to our previously reported NccS7073 knock-in mice, 30 the reduced total T58M-Ncc abundance may also be independent of the altered DCT cellular volume. Reminiscent of the markedly reduced total and phosphorylated Ncc expression in Wnk4 31 and Spak knockout 32 as well as kinase-dead Spak knock-in mice, 33 the constitutive inactivation of the Wnk4-Spak cascade may not only decrease Ncc phosphorylation but also reduce its accumulation in apical membranes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Reduced T60M-NCC expression in MDCK cells, markedly diminished Ncc abundance in the DCT cells of Ncc T58M/T58M mice, and decreased urinary NCC excretion, an index of membrane-expressed NCC, in GS patients all indicated that T60M led to reduced NCC expression primarily through post-translational modification (phosphorylation) rather than translational change. Because increased late DCT volume was found in Ncc T58M/T58M mice, similar to our previously reported NccS7073 knock-in mice, 30 the reduced total T58M-Ncc abundance may also be independent of the altered DCT cellular volume. Reminiscent of the markedly reduced total and phosphorylated Ncc expression in Wnk4 31 and Spak knockout 32 as well as kinase-dead Spak knock-in mice, 33 the constitutive inactivation of the Wnk4-Spak cascade may not only decrease Ncc phosphorylation but also reduce its accumulation in apical membranes.…”
Section: Discussionsupporting
confidence: 88%
“…50 The BPs of restrained conscious mice were measured with a programmable tailcuff sphygmomanometer (MK-2000A; Muromachi, Tokyo, Japan). 23,30,51 Hydrochlorothiazide, Furosemide, and Amiloride Challenge Studies…”
Section: Blood and Urine Analyses And Bp Measurementmentioning
confidence: 99%
“…The maintenance of a certain level of NCC phosphorylation may explain the rather mild phenotype of the I-1 2/2 mice. In contrast to patients with Gitelman syndrome and NCC-deficient mice as well as NCC knock-in mice bearing a Gitelman mutation (Ser707/X) 44 and SPAKdeficient mice, 45,46 the I-1 2 /2 mice have no secondary hyperaldosteronism, hypomagnesaemia, and hypocalciuria. However, I-1 2/2 mice tend to have a reduced thiazide response on dietary Na + restriction and a trend for slightly lowered plasma K + concentrations.…”
Section: Discussionmentioning
confidence: 96%
“…It is difficult to determine whether upregulation of Ca-transporting molecules is due to the salt supplement alone or if there is any contribution of a direct effect from thiazides. Recently, Yang et al (24) created a mouse model of Gitelman syndrome by knocking in a gene with a known point mutation of NCC (24). The phenotype of this mouse model is identical to human Gitelman syndrome: relatively hypotensive, hypokalemic, hypomagnesemic, and hypocalciuric.…”
Section: Discussionmentioning
confidence: 99%